GENDER INEQUALITY DEPICTED IN INDONESIAN BEST-SELLING NOVEL BEAUTY IS A WOUND - Halim, Nur Mutmainna; Dahniar, Dahniar; Halim, Abd; Anugrah, Indah; Pratiwi, Dian Fera (ELLITE, 2023)
This study focuses on the novel Beauty is a Wound, which was originally translated by Annie Tucker from the Indonesian novel Eka Kurniawan's Cantik Itu Luka (2002). This study was conducted to identify and analyze instances of gender inequality in "Beauty is a Wound." This study aims to: 1) identify the forms of gender inequality portrayed by women in Beauty is a Wound; and 2) the meaning behind inequality. The qualitative descriptive approach was adopted in this investigation. Mansour Fakih's (2013) idea is being utilized by researchers. The findings revealed that women face four categories of gender inequality: subordination (four), marginalization (six), violence (25), and stereotyping (five). In this study, the meaning of inequality is that (1) women's characters do not provide the same rights as other children to get education, study, and socialize; (2) prisoners appear helpless and do not have the right to manage their own lives, which results in marginalization; (3) they were subjected to poor treatment at the hands of Japanese soldiers, which resulted in both physical and psychological injuries, which led to the claim that it was violence; and (4) the assumption that they were vile individuals.